The Effect of Peer Bullying and Psychological Symptoms on the Quality of Life of Children and Adolescents with Juvenile Idiopathic Arthritis - Ustun, Nur Seda Gulcu; Ay, Elif Gumussoy; Yigit, Yasemin Demir; Gurgoze, Metin Kaya (Marmara Univ, Inst Health Sciences, 2025)
Objective: To the best of our knowledge, no previous study has investigated the relationship between peer bullying, depression, anxiety, and quality of life in children and adolescents with juvenile idiopathic arthritis (JIA). This study aims to examine how peer bullying and psychological symptoms affect quality of life in this population. Methods: Thirty children and adolescents diagnosed with JIA at a pediatric rheumatology clinic and 32 healthy controls without any chronic illnesses were included. Parents of participants with JIA completed a sociodemographic questionnaire and a parent-reported quality of life scale. The participants themselves completed self-report measures assessing bullying experiences, quality of life, anxiety, and depression. Results: Peer bullying, anxiety, and depression were more prevalent among JIA patients than in healthy controls, while their quality of life scores were significantly lower. Among patients with JIA, the presence of anxiety and depression was associated with reduced quality of life. Depression scores were higher in those who had experienced peer bullying compared to both non-bullied JIA patients and healthy controls. Additionally, physical functioning scores-a component of quality of life-were lower in the bullied group compared to non-bullied patients. Conclusion: These findings suggest that peer bullying may contribute to elevated levels of depression and anxiety, thereby negatively impacting the quality of life in children and adolescents with JIA. Routine screening for peer bullying and associated psychological symptoms in this population is recommended to enable early intervention and promote well-being. Further research with larger samples is needed to better understand the long-term effects of bullying in pediatric JIA patients.
Keywords: juvenile idiopathic arthritis; quality of life; peer bullying; anxiety; depression